IMPLEMENTASI SIMRS MENUJU SISTEM TERINTEGRASI DALAM MENINGKATKAN EFISIENSI OPERASIONAL PADA RS BHAYANGKARA KUPANG - Kristina; Rohendi; Juli Asril; Kristina Kristina; Rohendi Rohendi (Journal of Innovation Research and Knowledge, 2025)
Implementing SIMRS towards an integrated Hospital Management Information System (SIMRS) is important for improving operating effectiveness and moving healthcare services closer to being fully digital. Some parts of SIMRS are still not fully implemented across all service units at Bhayangkara Hospital Kupang. For example, patient registration, billing, and electronic medical records are already in use, but they are not fully linked across all service units yet. Service flow, teamwork between departments, and decision-making based on facts are all less effective because of this. Through in-depth interviews, field observations, and document readings, the study used a qualitative descriptive case study method.Findings show that there are several major problems with creating an integrated SIMRS. These include inadequate IT infrastructure, staff members who aren’t good with computers, the lack of standard operating procedures (SOPs) across departments, and the continuation of a culture of doing things by hand. These problems lead to more work for the staff, duplicate data, delays in service and reporting, and unhappy patients. To make sure that SIMRS is used consistently and effectively, the hospital’s management needs to come up with a full system development plan that includes strengthening internal policies, training staff, improving infrastructure, and putting together a cross-unit coordination team. Improving user skills and getting the technology infrastructure ready should be at the center of system development so that SIMRS can be used to its fullest potential. A fully integrated SIMRS should help with work speed, service data clarity, real-time management decision-making, and, in the end, better patient care at Bhayangkara Hospital Kupang